Assessing the mycotoxin producing potential of pathogens causing vegetable rots - and P. AHLUWALIA, SANGEETA GUPTA*, R. AGGARWAL (Indian Phytopathology, 2009)
A total of 389 fungal strains belonging to 18 species were isolated from chilli, pointed gourd, garlic, onion and potato. Aspergillus and Fusarium species showed wide occurrence on these vegetables. All fungal isolates had shown 3 to 18% rotting at 20ºC and 6 to 35% at 25ºC, which reached up to 82% at 30ºC and 85% relative humidity on their respective hosts. Maximum rotting was caused by Fusarium (upto 82%) followed by Aspergillus (upto 60%) and Alternaria (upto 42%). All isolates were subjected to preliminary detection of mycotoxin production and their chemical confirmation under in vitro conditions. Thirty seven to 67% isolates of Aspergillus spp., 14 to 40% of Fusarium sp. and 20-42% of Alternaria spp. were toxin producers. All the strains of Aspergillus species produced aflatoxin, while Fusarium spp. produced zearalenone.Maximum concentration of 1.2 to 6.4 ppm, aflatoxin B1 was produced by A. flavus of garlic, whereas 3.00 to 5.5ppm of aflatoxin B2 was produced by A. flavus isolated from onion. Maximum zearalenone (5.33 to 14.20 ppm) was elaborated by F. equiseti isolated from pointed gourd.